Analysing The Impact Of Product Completeness, Service Quality, And Price Discount on Consumer Purchasing Decisions at CV. Sarijaya Agro Pemalang - Adhitya Dwi Anggara; Sari Wiyanti; Yuniarti Herwinarni (JURNAL ECONOMINA, 2026)
The agribusiness sector has become more competitive, so companies must optimize their marketing strategies to increase consumer purchases. This study aims to analyze consumer purchasing decisions and the factors that influence them. This is a quantitative study, with the population consisting of consumers of CV. Sarijaya Agro Pemalang and a sample of 100 respondents. The sampling technique used was non-probability sampling via the accidental sampling method. The collected data were analyzed using SPSS software to test classical assumptions, perform linear regression analysis, and conduct hypothesis testing. The results indicate that all variables—product completeness, service quality, and price discounts—influence purchasing decisions both partially and simultaneously